The Improving Civics Learning Outcomes through Group Discussion Methods and Observation Sheets on Indonesian Human Rights Enforcement Materials - Hotmaida Simanjuntak; Monalisa Siahaan; Rince Marpaung; Elizabeth Tinambunan (Bulletin of Science Education, 2024)
The aim of this research is to improve student learning outcomes through group discussion methods and observation sheets on Indonesian human rights enforcement material in the Civics learning process. The main basis for this research is that the learning difficulties experienced by students result in a decrease in enthusiasm for learning, apart from being caused by methodological inaccuracies, it is also rooted in the use of learning methods that tend to be monotonous and lack of evaluation in the civics education (PKn) learning process with human rights material. Action Research Kelas (Classroom Action Reseach) and a qualitative descriptive approach was applied in this research in an effort to resolve the problems or difficulties faced by students. This research was carried out at the Smart Mandiri Medan Private Vocational School, Jalan Cemara Abadi, Sampali Village, Percut Sei Tuan District, Deli Serdang. Based on students' Civics learning results which have increased starting from the pretest test, learning results test in cycle I, learning results test in cycle II, the test items tested have experienced learning completeness. In other words, because the overall results of students' Civics learning and the questions tested on students have been completed, the learning process using the discussion learning method is stopped until cycle II. From the data obtained, up to the learning outcomes in cycle II, it can be concluded that there has been an increase in Civics learning outcomes through the group discussion method on Human Rights material in class